Przeciwdziałanie nieuczciwym praktykom rynkowym w łańcuchu dostaw żywności w prawie włoskim - Kapała, Anna (Wydawnictwo Naukowe UAM, 2017)
The aim of the article is to familiarise Polish readers with the Italian regulations on counteracting unfair commercial practices in the food supply chain. Currently this issue is addressed by thhe Italian Law No 27/2012, which has been subject of doctrinal criticism, legislative changes and judicial decisions. There are still several issues that raise questions of interpretation, including the scope of its subject-matter or failure to comply with the written form which invalidates the contract and whether, in order to classify the practices as unlawful, it is necessary to determine the conditions of a “significant trade imbalance” and a “deliberate abuse” of a dominant position by a stronger party to the contractual relationship.

L’articolo si propone di presentare al pubblico polacco la regolazione italiana riguardante le misure volte a combattere le pratiche commerciali sleali nella filiera agroalimentare. La problematica in oggetto è stata affrontata nella legge n. 27/2012, la quale è stata oggetto di critiche dottrinali, modifiche legislative e pronunce giurisprudenziali. Alcune questioni tuttora continuano a suscitare dubbi interpretativi, tra i quali il problema di ambito di applicazione, un dubbio se la mancanza della forma scritta dei contratti ne determini la nullità, e se per considerare le pratiche illegali, debbano presentarsi presupposti di “forte squilibrio commerciale” e di “abuso volontario” della posizione dominante da parte del contraente più forte nel rapporto contrattuale.
Combating unfair market practices in the food supply chain under Italian law
e misure volte a combattere le pratiche commerciali sleali nella filiera agroalimentare nel diritto italiano